Ensino de genética e evolução para entendimento da diversidade - Carla Patricia Fonseca Costa (2019)
Diversity is a property of living organisms, but in humans some differences are often the object of prejudice and discrimination. Genetics and Evolution are the branches of Biology that study heredity and the mechanisms that generate, maintain, increase or reduce diversity. This research aimed at creating and performing a teaching sequence (SD) for High School students about Evolution and the mechanisms that generate the diversity of living beings. The expectation is that these students would assimilate this knowledge and apply it in their daily life, hopefully presenting a more tolerant attitude towards human differences than it is unfortunately still common. The SD comprises four activities developed during seven 50 minutes classes for the same group of students. The activities analyses were carried out on data collected from its application to 3rd year High School students. Questionnaires were applied: a structured one, about evolution and biological diversity, other semistructured ones, asking about attitudes on hypothetical situations involving people diversity, and also a questionnaire about the students' perception regarding the teaching sequence. The content and categorization of these data were analyzed using content analysis. In addition to the questionnaires, students' commitment and behavior during the discussions and performance in the activities were also observed and written down. The results allowed us to conclude that the SD reached the goals expected in the group in which it was applied. The students were able to develop the activities and understand the fundamental concepts involved in the diversity of living organisms.